ChemInform Abstract: A One‐Pot Cross‐Pinacol Coupling/Rearrangement Procedure. Issue 10 (7th March 2013) - Scheffler, Ulf; Mahrwald, Rainer
Abstract In the first step, diols (III) are formed which are deoxygenated by pinacol rearrangement to afford the corresponding ketones with high regioselectivity favoring (IV).